Posted by sh on Friday, October 29, 2010 at 10:06pm.
no, the second part of your product rule is not correct
lets just differentiate
1 - 4^x
that would be (-4^x)(ln4)
my final answer would be
f '(x) = (1-4^x) + x(-4^x)(ln4)
= 1 - 4^x - x(ln4)(4^x)
So the negative is not included,
for example f(x)=-2^x
f'(x) would be (-2^x)(ln2)?
I think you got it.
in your example you could look at -4^x
Calculus - derivatives - Okay, I want to find the derivative of (x^x)^(x^x)... ...
Calc - a) y =ln(x-1) find dy/dx=? b) y=3 ln x - ln (1/x) where x >0, dy/...
Calculus - Find the derivative of y = ln |cos(ln)|. I got -tan(ln x)/x, is this ...
Calculus I - Find the derivative of y=ln((1+e^x)/(1-e^x)) I know that the ...
maths - How do I find the derivative of ln(ln(1-x))? I know that the derivative ...
calculus - Would the derivative of ln(x^2) be 1/x^2? and also the derivative of ...
Math - Find the derivative of: ln(2x/x+1) the answer is 1/x(x+1) but i can't...
Calculus - Find the derivative Y = ln(ln^2(ln^2 x))
calculus - find the derivative of f(x)= ln ln ln x
CALCULUS - what is the derivative of ln(x-1)? If you are studying the calculus ...
For Further Reading